2014
DOI: 10.1186/1746-4269-10-58
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring durum wheat diversity in the reality of traditional agricultural systems: varieties, seed management, and farmers’ perception in two Moroccan regions

Abstract: BackgroundTraditional agrosystems are the places were crop species have evolved and continue to evolve under a combination of human and environmental pressures. A better knowledge of the mechanisms underlying the dynamics of crop diversity in these agrosystems is crucial to sustain food security and farmers’ self-reliance. It requires as a first step, anchoring a description of the available diversity in its geographical, environmental, cultural and socio-economic context.MethodsWe conducted interviews with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…But in these studies, no other information than geographical location and large scale agro-ecological conditions was incorporated. Chentoufi et al [ 48 ] recently conducted interviews with farmers from the Pre-Rif and the oases of the Atlas Mountains. They inventoried the varietal names and described their geographical distribution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…But in these studies, no other information than geographical location and large scale agro-ecological conditions was incorporated. Chentoufi et al [ 48 ] recently conducted interviews with farmers from the Pre-Rif and the oases of the Atlas Mountains. They inventoried the varietal names and described their geographical distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Among their key results, they evidenced that the seed was in majority produced on farm, and that exchange practices included a combination on (mainly) purchase from local markets, supply from friends and relatives, and rarely, supply of modern varieties from agricultural extension offices. In these regions, modern varieties have indeed been introduced at variable levels and Chentoufi et al [ 48 ] showed that they were integrated into the traditional practices of seed exchange and management. Nevertheless, farmers clearly distinguished traditional from modern varieties, and appreciated the traditional varieties especially for the straw and the quality for food processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). The characterization and the evaluation of crop varieties allow us to protect and restore this genetic heritage .To be used at the end in breeding programs (Chentoufi et al;2014). Cereal improvement has long been and still is strongly oriented towards increasing productivity ( Boubaker et al ;1999).…”
mentioning
confidence: 99%
“…This result could be explained by climatic variations, including temperature and rainfall in the region. This hypothesis does not exclude, however, the specific genetic value of cultivars (Chentoufi et al, ). The weight of 1000 grains is significantly influenced by irrigation treatments, which marked changes of grain weights between 22.2 and 37.9 g. Our findings in this context are in agreement with the study of Chahbar and Belkhodja ().…”
Section: Resultsmentioning
confidence: 99%